A problem of fetal age estimation - Hajnowska-Cieślik, Krystyna; Marecki , Bogusław (Anthropological Review, 1980)
Lack of a reliable method for ascertdining age of human fetuses seriously impedes studies on fetal ontogeny. Age of fetus with unknown calendar age is estimated by comparing its total length or crown-rump length to a standard value. The authors present here an attempt at evaluation of accuracy of eight sets of such standards. Their material consists of 630 fetuses of age known from mother's. information on date of last menstruation prior to pregnancy. Age of each fetus has been estimated with use of eight various standards. Comparison of results obtained by application of various standards, conducted with use of t test, showed exisence of considerable discrepancies between ages estimated by means of different standards. There were also found considerable differences between estimated ages and actual age of fetuses. These results enable authors to conclude that there is a need for more accurate standards pertaining to a population wherefrom fetuses to be worked with originate and based on several somatic traits most commonly examined.